Knowledge Transfer for Handovers of Complex Infrastructure Projects - Johansson, Madeleine (My University, 2023)
The handover process is an important process at the end of a project and implies next to the delivery of the product, the handover of documentation, guidelines as well as knowledge. The transfer of knowledge in the handover process is a challenge in ordinary construction projects but becomes even more challenging in complex infrastructure projects. The size and complexity of these projects, result in a large amount of documentation that is managed and transferred from the project to the receiving organizations. Moreover, construction knowledge is often tacit, which is retained by the individuals and organizations involved in the construction project, and finally is lost once the project is completed. Not much has been published about the handover process in relation to knowledge transfer. In project management literature, there are publications about the close-out phase in construction projects, which is the last phase in the project lifecycle. However, there has rarely been anything published about how complex infrastructure projects should be handed over in relation to knowledge transfer. Therefore, this topic is relevant to be studied. The purpose of the thesis is to investigate how knowledge is managed, stored and transferred from the project to the receiving organizations. The thesis aims to map challenges related to knowledge transfer for handovers, and to produce improvement proposals that the Swedish Transport Administration (STA) and other public clients can benefit from. The aim of the thesis was fulfilled through a qualitative research approach by conducting 18 semi-structured interviews with representatives from STA with experiences of handovers of complex infrastructure projects. Moreover, a literature study was conducted to map the current practices, opportunities, and challenges with knowledge transfer for handovers of complex infrastructure projects. Further, different applied and conceptual models for learning and knowledge transfer were investigated. The results showed that the main challenges are organizational and communication challenges in the handover process. Further, the findings show that explicit knowledge is handled relatively well in the process, but that tacit knowledge is more difficult and has challenges. Furthermore, the main possible improvements that were identified are maintaining competence from the project to the receiving organizations, by changing the organizational structure and conducting education. Finally, this thesis has created a foundation for further research of knowledge transfer for project handovers, and especially of complex infrastructure projects.
Keywords: Knowledge management; knowledge transfer; explicit knowledge; tacit knowledge; project handover; project close-out; complex infrastructure projects; construction.